Environmental factors affecting a football`s trajectory at the direct free kick - Marqversen, E. M.; Krustrup, P.; Andersen, T. B. (Sports Engineering, 2023)
When football players travel the world for international matches, the environmental factors change. These factors affects the ball`s trajectory. The aim of this study was to highlight how changes in altitude, temperature, air humidity and gravitational pull affect the players` scoring probability when performing a direct free kick from 25 m. Based on theoretical models by Bray and Kerwin, and Myers and Mitchell, adjusted models were used to find the theoretical displacement in goal crossing position with varying environmental factors. This displacement was compared to the probability distribution of six professional football players from the top Danish league, each doing 10 free kicks at their home stadium. The free kicks were tracked using radar and all needed variables and initial conditions for the adjusted models were measured. The results show no significant changes in scoring probability when theoretically moving the players probability distribution to fit the environment of four different historic FIFA or UEFA finals. When adjusting the data of mean goal crossing position to the players` aim points or orientation of their probability distributions, significant changes were found. In conclusion, it was found that a highly accurate player would theoretically experience significant changes to the scoring probability when the altitude or temperature changes compared to their home court.